Mutational analysis of the encephalomyocarditis virus primary cleavage. - Hahn, H (1996)
Sixteen substitution mutations of the conserved DvExNPGP sequence, implicated in cardiovirus and aphthovirus primary polyprotein cleavage, were created in encephalomyocarditis virus cDNA, expressed, and characterized for processing activity. Nearly all the mutations severely decreased the efficiency of the primary cleavage reaction during cell-free synthesis of viral precursors, indicating a stringent requirement for the natural sequence in this processing event. When representative mutations were tested in full-length genomic contexts, they were lethal and no revertants were observed. Not only were the primary cleavage reactions deficient in these polyproteins, but subsequent cleavage of P1 by endogenous or exogenous 3C pro was also impaired. This indicates that primary cleavage has a role in the proper processing of the viral capsid precursor.